Diffusion of Intraperitoneal Chemotherapy in Women with Advanced Ovarian Cancer in Community Settings 2003–2008: The Effect of the NCI Clinical Recommendation - Bowles, Erin J.; Wernli, Karen J.; Gray, Heidi J.; Bogart, Andy; Delate, Thomas; O'Keeffe-Rosetti, Maureen; Nekhlyudov, Larissa; Loggers, Elizabeth T. (Frontiers in Oncology, 2014)
Purpose: A 2006 National Cancer Institute (NCI) clinical announcement recommended the use of combined intravenous (IV) and intraperitoneal (IP) chemotherapy over IV chemotherapy alone for women with International Federation of Gynecology and Obstetrics (FIGO) stage 3 optimally debulked ovarian cancer due to significant survival benefit demonstrated in multiple randomized clinical trials. We examined uptake of IP chemotherapy in community practice before and after this recommendation. Methods: We identified 288 women with FIGO stage 2 or greater incident ovarian cancer diagnosed from 2003 to 2008 at three integrated delivery systems in the US. Administrative health plan data were used to determine patient characteristics and receipt of IV and IP chemotherapy within 12 months of diagnosis. We compared characteristics of women receiving IV chemotherapy alone versus IP chemotherapy (with or without IV chemotherapy) and assessed temporal trends in IP chemotherapy use. Results: Overall 12.5% (n=36) of women received IP chemotherapy during the study period. IP chemotherapy use was nonexistent between 2003 and 2005. Use of IP chemotherapy occurred among 26.9% of women diagnosed in 2006 and plateaued at 20.4% of women diagnosed in 2008. IP recipients were younger (mean age 55.9 vs 63.5 years, p=< 0.001) and more likely to have stage 3 ovarian cancer (77.8% vs 50.4% p=0.039) compared to their IV-only chemotherapy counterparts. Conclusions: Use of IP chemotherapy for newly diagnosed advanced stage ovarian cancer patients was uncommon in this community setting. Future research should identify potential patient, physician, and system barriers and facilitators to using IP chemotherapy in this setting.